Identifikasi Cendawan Pascapanen Pada Jagung Pakan Ternak yang Dijual Pengecer Di Kota Banjarbaru - Laodja, Zahra Fauziyyah; Fitriyanti, Dewi; Aidawati, Noor (JURNAL PROTEKSI TANAMAN TROPIKA, 2025)
Corn (Zea mays L.) is one of the main food sources for the world's population, besides being used as animal feed. However, the problem is that the feed corn field is easily contaminated by post-harvest fungi. The aim of this research is to identify fungi that infect post-harvest feed corn circulating in Banjarbaru City. The research method used purposive sampling which was carried out at the Phytopathology Laboratory, Department of Plant Pests and Diseases, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru. The results of the research showed that there were post-harvest fungi in animal feed corn, Aspergillus flavus with 15 isolates, Aspergillus niger with 10 isolates, Penicillium sp. 2 isolates, Fusarium sp. 6 isolates, and Rhizoctonia sp. 1 isolate, resulting in 34 isolates from corn that were symptomatic and asymptomatic. Three types of fungi are contaminant fungi and produce mycotoxins, Aspergillus sp., Fusarium sp., and Penicillium sp.